Imagining the Arab other how Arabs and non-Arabs view each other - Djedidi, Tahar Labib (Library of modern Middle East studies, 2008)
Seeks to understand how the 'Other' is viewed in Arab culture, and vice versa. This work examines how Turks, Europeans, Christians and Iranians have been represented in the arts, opinions and cultures of the Arab world. Conversely, it also explores the intellectual representation of 'The Arab' in other cultures.